2022
DOI: 10.1021/acs.analchem.2c03731
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Monitoring of Nitric Oxide Release in the Mouse Colon Using a Boron-Doped Diamond Microelectrode Modified with Platinum Nanoparticles and Nafion

Abstract: This research reports on the preparation of a boron-doped diamond microelectrode modified with platinum nanoparticles and Nafion and its application for detecting nitric oxide (NO) in vitro in the mouse colon. Platinum nanoparticle deposition was performed potentiodynamically using a 2.0 mmol L −1 potassium hexachloroplatinate solution and cycling from −0.2 to 1.3 V vs Ag/AgCl at 0.01 V s −1 for 10 cycles. The Nafion overlayer was applied by immersion in a solution containing 2.5% (w/v) colloidal Nafion and dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…This tactic was previously used to enhance the sensitivity and stability of ATP biosensors 52 and to platinize boron-doped diamond microelectrodes. 38 These electrodeposition conditions produce a dispersed coverage of Pt nanoparticles across the substrate with a range of diameters. This is characteristic of a progressive nucleation and growth process in which new nuclei continuously form while existing Pt nanoparticles grow out of those nucleation sites.…”
Section: ■ Experimental Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…This tactic was previously used to enhance the sensitivity and stability of ATP biosensors 52 and to platinize boron-doped diamond microelectrodes. 38 These electrodeposition conditions produce a dispersed coverage of Pt nanoparticles across the substrate with a range of diameters. This is characteristic of a progressive nucleation and growth process in which new nuclei continuously form while existing Pt nanoparticles grow out of those nucleation sites.…”
Section: ■ Experimental Methodsmentioning
confidence: 99%
“…To increase the electrochemically active area of the electrode and improve adhesion of the multienzyme film, , the Pt microelectrodes were potential cycled in a solution containing 2 mmol L –1 K 2 PtCl 6 in 0.5 mol L –1 H 2 SO 4 from −0.2 to 1.2 V at 10 mV s –1 for 10 cycles with an initial potential of 1.0 V scanning cathodically to reduce Pt­(IV) and initiate nanoparticle nucleation. This tactic was previously used to enhance the sensitivity and stability of ATP biosensors and to platinize boron-doped diamond microelectrodes . These electrodeposition conditions produce a dispersed coverage of Pt nanoparticles across the substrate with a range of diameters.…”
Section: Experimental Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Henderson Skye et al [20] investigated the preparation of nanoparticles and Nafionmodified boron-doped gold BDD microelectrodes and their application in the in vitro detection of nitric oxide ( NO ) in mouse colon; Boonkaew Suchanat et al [21] proposed boron/nitrogen co-doped diamond-graphene nanowall-structured ( DGNW ) integrated with screen-printed graphene electrode ( SPGE ) for the detection of serotonin ( 5-HT ) as a model system and applied the method to synthetic urine samples, the results showed that the DGNW modified electrode has good anti-pollution properties and biocompatibility; while Dushna Olha et al [22] firstly combined a working boron-doped diamond electrode ( BDDE ) with a novel screen-printed sensor to form a planar electro chemical cell consisting of a working boron-doped diamond electrode ( BDDE ) and a novel screen-printed sensor was first used for voltammetric determination of the alkaloid atropine (ATR).…”
Section: Detection Of Trace Organic Compound Componentsmentioning
confidence: 99%